Supporting Struggling Grade 8 Science Students’ Motivation, Participation and Performance through Peer-Tutoring Approach - Bellen, Joy A.; Jomoc, Amalia B. (Annals of Tropical Research, 2017)
Research shows that cognitive and affective abilities among science students can be enhanced using peer tutoring approach. However, peer tutoring approach remains an underutilized peer support (Bond & Castagnera 2006). This study determined the effects of peer tutoring approach in motivation, participation and academic performance of grade 8 students. Using regression discontinuity design, the respondents were non-struggling, struggling who accepted peer tutoring and struggling students who declined peer tutoring. Results showed that struggling students who accepted peer tutoring showed better participation, expertlike perceptions of junior high school science, and exam performance relative to their peers who were not attending the peer tutoring sessions. The results of this study provide evidence to teachers who want to plan targeted peer support for students who are struggling in junior high school science.